2006
DOI: 10.1111/j.1464-410x.2006.06501.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐clinical evidence for the use of phosphodiesterase‐5 inhibitors for treating benign prostatic hyperplasia and lower urinary tract symptoms

Abstract: OBJECTIVE To evaluate the potential of sildenafil, vardenafil and tadalafil, all phosphodiesterase‐5 (PDE‐5) inhibitors used for treating erectile dysfunction, for treating benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS). MATERIALS AND METHODS The mRNA expression of the PDE‐5 was determined in rat LUT tissues. The PDE‐5 inhibitors were also tested in organ‐bath experiments and in a partial bladder outlet obstruction (BOO) rat model in vivo. RESULTS The highest PDE‐5 mRNA expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 27 publications
7
128
0
8
Order By: Relevance
“…The same study demonstrated inhibition of human prostate stromal cell proliferation with vardenafil in vivo. 23 Tinel et al 24 utilized a rat model that demonstrated a PDE-inhibitor dosedependent reduction in smooth muscle contraction of bladder, urethral and prostate strips. A reduction in bladder nonvoiding contractions was noted in the rat BOO model after administration of sildenafil and vardenafil.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 99%
“…The same study demonstrated inhibition of human prostate stromal cell proliferation with vardenafil in vivo. 23 Tinel et al 24 utilized a rat model that demonstrated a PDE-inhibitor dosedependent reduction in smooth muscle contraction of bladder, urethral and prostate strips. A reduction in bladder nonvoiding contractions was noted in the rat BOO model after administration of sildenafil and vardenafil.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 99%
“…If cAMP-dependent signaling is favored in the presence of a α1-blocker, this could increase cGMP levels initially stimulated by tadalafil, which had until then remained functionally silent. Such positive cross-talk mechanism between cGMP and cAMP signaling previously described in other systems, could be the origin of the enhanced relaxant effect of the combination (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 98%
“…93 Experimental models, in human and rat tissue, have shown that PDE5 inhibitors decrease nonvoiding bladder contractions. 94,83 In addition, PDE5 inhibitors have been shown to improve urodynamic parameters in SCI patients. 82 PDE5 inhibitors offer an opportunity to treat ED and LUTS concurrently.…”
Section: Discussionmentioning
confidence: 99%